Technology for evidence-based cognitive behavioural supervision: new applications and research to improve organizational support. (14th October 2016) - Rousmaniere, Tony
Abstract: There has recently been an increasing call for new research and development in cognitive behavioural supervision, particularly in the area of evidence-based clinical supervision. New developments in supervision technology offer the potential to answer this call by providing greater objective measurement and corrective feedback in supervision. In this article, two new technologies that hold particular promise in this area are described: software for routine outcome measurement and videoconference for internet-based live one-way-mirror supervision. Notable challenges involved in supervision technology are discussed, and an example of technology being integrated into a graduate clinical training programme is described.